2021
DOI: 10.2147/eb.s272326
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-Ophthalmic Complications of Vestibular Schwannoma Resection: Current Perspectives

Abstract: Vestibular schwannomas (VSs), also called acoustic neuromas, are benign intracranial neoplasms of the vestibulocochlear (VIII) cranial nerve. Management options include “wait-and-scan,” stereotactic radiosurgery and surgical resection. Due to the proximity of the VIII nerve to the facial (VII) nerve in the cerebello-pontine angle, the VII nerve is particularly vulnerable to the effects of surgical resection. This can result in poor eye closure, lagophthalmos and resultant corneal exposure post VS resection. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…. The abducent nerve (VI) is affected by large vestibular shwannoma followed by an increased intracranial pressure with damge to CN-VI intra-operatively or due to trauma causing exposure keratitis 16 . Studies haves reported to have managed 45% of such cases conservatively with use of eye lubricant and eye shield only while 40-45% required surgeries to manage 17. We recorded CP Angle Meningioma 8 (16.7%) cases with Two cases had Brainstem contusion with hemeperisis (posttraumatic).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…. The abducent nerve (VI) is affected by large vestibular shwannoma followed by an increased intracranial pressure with damge to CN-VI intra-operatively or due to trauma causing exposure keratitis 16 . Studies haves reported to have managed 45% of such cases conservatively with use of eye lubricant and eye shield only while 40-45% required surgeries to manage 17. We recorded CP Angle Meningioma 8 (16.7%) cases with Two cases had Brainstem contusion with hemeperisis (posttraumatic).…”
Section: Discussionmentioning
confidence: 99%
“…The abducent nerve (VI) is affected by large vestibular shwannoma followed by an increased intracranial pressure with damge to CN-VI intraoperatively or due to trauma causing exposure keratitis 8,16 . Studies haves reported to have managed such cases conservatively while 40-45% of the comlications required surgeries to manage, 9,16 Vestibular Schwannoma with Hydrocephalus are managed with Ventriculo-Peritoneal Shunt. Obstructive hydrocephalus with acoustic neuroma as result of compression of 4 th ventricle by the CP anlgle tumor.…”
mentioning
confidence: 99%
“…The treatment of malignant cancers is vigorously pursued with precision, while the possible complications of thrombi are often ignored. , The occurrence and development of thrombi are closely related to the tumor . Many clinical and biological risk factors make tumor patients vulnerable to thrombi, including intravenous drug injection, surgical excision, laser irradiation, etc .…”
mentioning
confidence: 99%